Marine environment and maritime safety assessment using Port State Control database - Chuah, Lai Fatt; Mokhtar, Kasypi; Abu Bakar, Anuar; Othman, Mohamad Rosni; Osman, Nor Hasni; Bokhari, Awais; Mubashir, Muhammad; Abdullah, Mohd Azhafiz; Hasan, Mudassir (Elsevier BV, 2022)
Port State Control (PSC) is the inspection of foreign ships in national ports assists in the removal of substandard ship commerce from the global sea and ensures that no ship poses a threat to maritime safety and the marine environment. When a clear ground is discovered during an inspection, the inspector has the authority to detain the ship until the flaws are corrected in order to assure safety and reduce pollution hazards. This paper adopted a traditional literature review method using the selected six (6) years data from the inspections conducted by maritime authorities from 2016 to 2021 and incorporate with qualitative and quantitative analysis to ascertain the influence of each risk factor on the number of arrests, including the relationship between risk factors and the type of detain deficiency, which is a critical part of the study. This study's findings provide important insights into how to facilitate an effective way in selecting the ship to be inspected, followed by identifying the ship's risk profile and designing the inspection area, which plays a critical role in assisting the inspector in terms of time efficient and effective inspection (especially for the ships, which have a short duration at berth) during inspection to further strengthen maritime safety, ship's safety, seafarers' health and marine environmental protection